Strategic multimodal non‐invasive assessment of cardiac performance in patients with heart failure - Mi‐Jeong Kim; Jung Sun Cho; Kyusup Lee; Woojin Kwon; Chaeryeon Ohn; Myunhee Lee; Dae‐Won Kim; Tae‐Seok Kim; Mahn‐Won Park (ESC Heart Failure, 2023)
Abstract Aims Although various non‐invasive cardiac examinations are known to be predictive of long‐term outcomes in patients with heart failure (HF), combining them properly would provide synergism. We aimed to show that non‐invasive cardiac assessments targeting left ventricular filling pressure (LVFP), left atrial remodelling, and exercise capacity would provide better prognostication in combination. Methods and results This prospective observational study included consecutive hospitalized stage A–C HF patients evaluated with N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP), echocardiography including two‐dimensional speckle tracking, and cardiopulmonary exercise testing. According to NT‐proBNP and echocardiographic semi‐quantitative LVFP grading (Echo‐LVFP), patients were classified into three LVFP groups: normal range of both Echo‐LVFP and NT‐proBNP (Group 1), normal range of Echo‐LVFP but elevated NT‐proBNP (Group 2), and elevated Echo‐LVFP and NT‐proBNP (Group 3). The adverse outcome was defined as a composite of cardiovascular death, non‐fatal acute coronary syndrome, acute stroke, or HF‐related hospitalization. Among 224 HF patients (mean age of 63.8 ± 11.6 years, 158 men) analysed, 160 (71.4%) had ischaemic aetiology. During the follow‐up of 18.6 ± 9.8 months, event‐free survival in Group 2 (n = 56, age of 65.4 ± 12.4) was better than that in Group 3 (n = 45, age of 68.5 ± 11.5) but worse than that in Group 1 (n = 123, mean age of 61.4 ± 10.5) (log‐rank P < 0.001). Mechanical left atrial dysfunction (peak longitudinal strain <28%) (adjusted hazard ratio 5.69, 95% confidence interval 1.06–4.48) and limited exercise capacity (peak VO2 per +5 mL/kg/min) (adjusted hazard ratio 0.63, 95% confidence interval 0.46–0.87) were also predictable adverse outcomes. Serial addition of peak VO2 and left atrial strain to the model incrementally enhanced the predictive power of LVFP‐based risk stratification for adverse outcomes. Conclusions The combination of NT‐proBNP and Echo‐LVFP could be used to predict adverse outcomes in patients with HF of various stages. Left atrial mechanics and exercise capacity are incremental to prognostication. Non‐invasive test findings could be strategically combined to provide an integrative profile of cardiac performance.